Skeletal Birth Injuries: Presentation, Management and Outcome at the University College Hospital, Ibadan - Ogunlade SO; Omololu AB; Alonge TO; Ifesanya AO (Nigerian Journal of Paediatrics, 2024)
Background: Birth injuries are not uncommon in newly born babies. Such injuries which are sometimes first detected by the parents after discharge of the baby from the hospital, often cause a lot of anxiety regarding the causes and prognosis.